2013
DOI: 10.1016/j.neuint.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins K interact with N-terminus α-synuclein and modulate the protein fibrillization in vitro. Exploring the interaction between quinones and α-synuclein

Abstract: In the last decades, a series of compounds, including quinones and polyphenols, has been described as having anti-fibrillogenic action on α-synuclein (α-syn) whose aggregation is associated to the pathogenesis of Parkinson's disease (PD). Most of these molecules act as promiscuous anti-amyloidogenic agents, interacting with the diverse amyloidogenic proteins (mostly unfolded) through non-specific hydrophobic interactions. Herein we investigated the effect of the vitamins K (phylloquinone, menaquinone and menad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 63 publications
2
27
0
1
Order By: Relevance
“…We note here that Lys specific molecular tweezers have been reported to be capable of inhibiting the aggregation of various amyloidogenic peptides [81]–[84]. 1,4-napthoquinone based inhibitors were also found to interact with Lys residues and efficiently reduced the fibrilisation propensity of αSyn [85]. Thus, our observation of the importance of the Lys repeats in the cross dimerization may be used for designing drugs targeted at inhibiting A β -αSyn co-assembly.…”
Section: Discussionmentioning
confidence: 67%
“…We note here that Lys specific molecular tweezers have been reported to be capable of inhibiting the aggregation of various amyloidogenic peptides [81]–[84]. 1,4-napthoquinone based inhibitors were also found to interact with Lys residues and efficiently reduced the fibrilisation propensity of αSyn [85]. Thus, our observation of the importance of the Lys repeats in the cross dimerization may be used for designing drugs targeted at inhibiting A β -αSyn co-assembly.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies have demonstrated a regulatory role for quinone formation in DA neurons in the L-DOPA-treated PD model induced by neurotoxins and in methamphetamine neurotoxicity ( Asanuma et al, 2003 ; Miyazaki et al, 2006 ; Ares-Santos et al, 2014 ). DA quinones can modify a number of PD-related proteins, such as α-synuclein (α-syn), parkin, DJ-1, Superoxide dismutase-2 (SOD2), and UCH-L1 ( Belluzzi et al, 2012 ; Girotto et al, 2012 ; da Silva et al, 2013 ; Hauser et al, 2013 ; Toyama et al, 2014 ; Zhou et al, 2014 ) and have been shown to cause inactivation of the DA transporter (DAT) and the TH enzyme ( Kuhn et al, 1999 ; Whitehead et al, 2001 ), as well as mitochondrial dysfunction ( Lee et al, 2003 ), alterations of brain mitochondria ( Gluck and Zeevalk, 2004 ) and dysfunction in Complex I activity ( Jana et al, 2007 , 2011 ; Van Laar et al, 2009 ). Additionally, DA quinones can be oxidized to aminochrome, whose redox-cycling leads to the generation of the superoxide radical and the depletion of cellular nicotinamide adenine dinucleotide phosphate-oxidase (NADPH), which ultimately forms the neuromelanin ( Sulzer et al, 2000 ) known to be accumulated in the SNpc of the human brain ( Ohtsuka et al, 2013 , 2014 ; Plum et al, 2013 ).…”
Section: Dopamine Metabolismmentioning
confidence: 99%
“…84 Vitamin K has also been shown to have a beneficial role in the modulation of α-synuclein fibrillization, associated with PD. 85 Increased dietary vitamin K intake has been associated with less severe subjective memory complaints in the elderly. 86 Vitamin B synthesis increases as the intestinal microbiota are being established 87 with deficiencies leading to serious neurological disorders including beri-beri, polyneuropathy and cerebellar ataxia.…”
Section: Gut Microbiota-derived Metabolites Influencing Bbb Integritymentioning
confidence: 99%